Examining the relationship between spiritual health and mental health with drug addiction among the student population in central Iran - Fariba Dehghanizade; Mohammad-Javad Azadchehr; Alireza Shah-Fazl; Abdollah Omidi; Razieh Eghtesadi; Hamid Reza Banafshe; Amir Ghaderi (Journal of Multidisciplinary Care, 2023)
Background and aims: It has been nearly a century since human society has been determined to find a fundamental solution to the problem of drug addiction, as one of the fundamental problems of human life. Therefore, this study was conducted to determine the relationship between spiritual and mental health and the tendency to addiction in the student population of Kashan. Methods: In this Analytical cross-sectional research, the statistical population included the 600 participants of students aged 18 to 35 in Kashan city, and Simple Random Sampling was done from universities of medical sciences, Islamic Azad University, and Kashan University in 2018-2019. The students completed questionnaires about spiritual health, mental health, and the tendency to use drugs, and the results obtained after collecting and recording were analyzed by statistical tests using SPSS version 26 software. Results: The average scores of the students in terms of mental health, spiritual health, spiritual health from the perspective of Islam, and readiness for addiction were 1.01±0.70, 75.10±20.83, 86.43±21.26 and 30.95±20.34, respectively. Spiritual health, spiritual health from the perspective of Islam, and readiness for addiction were related to the age (P<0.05), gender, educational level (P<0.05), and marriage (P<0.001) of the students. Conclusion: Considering the positive and significant role of spiritual health in mental health, strengthening the spiritual dimension can improve mental health, reduce mental disorders, reduce the desire to use drugs, and continue the course of addiction treatment.